--------------------------------------------------------------------------------

ok. How the hell do you apply the descriminant (B^2 - 4ac) to an equation like this:

x^2 + (k-2x)^2 - 3x - 4 = 0

with intentions of finding the value of k.

The question says that y+2x=k is tangent to circle x^2 + y^2 -3x - 4 = 0. And to find the value of k (7 marks) .

In the anwswer booklet it says "x^2 + (k-2x)^2 - 3x - 4 = 0 apply to descriminant"

HELP exam is tomorrow:|

**0**

# HElp day before exam!

Started by gsmushet1, May 18 2006 10:31 PM

5 replies to this topic

### #1

Posted 18 May 2006 - 10:31 PM

### #2

Posted 18 May 2006 - 10:36 PM

i would break the bracket and get k^2 - 4kx + 4x^2 this means we now have

5x

a=5

b=-7-4k

c=k

5x

^{2}+(-4k-7)x+(k^{2}-4)=0a=5

b=-7-4k

c=k

^{2}-4If i am not here i am somewhere else

### #3

Posted 18 May 2006 - 10:37 PM

Expand the (k-2x)² bracket and simplify the expression, separate the x² terms, x and numberical terms. k is a number so if you get that on it own or a multiple of that without x in the value, just separate it, and group like terms together. I'd go in depth, but someone's bound to post soon enough anyway!

__University of Strathclyde Homepage__

CPU-Z snapshot

CPU-Z snapshot after OC

3D Mark 2006 results

3D Mark 2006 results after OC

3D Mark 2003 Results

3D Mark 2003 results after OC

### #5

Posted 18 May 2006 - 11:04 PM

yeah u do doesnt change anything though

a=5

b=-7-4k

c=k

a=5

b=-7-4k

c=k

^{2}-4If i am not here i am somewhere else

### #6

Posted 19 May 2006 - 01:51 PM

Ach nevermind, it's over now and i'm SURE of an A=)

#### 1 user(s) are reading this topic

0 members, 1 guests, 0 anonymous users